2011
DOI: 10.1182/blood-2011-04-350793
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced levels of both the membrane-bound and soluble forms of IgM Fc receptor (FcμR) in patients with chronic lymphocytic leukemia

Abstract: The association of an IgM-Fc receptor (FcR) with chronic lymphocytic leukemia (CLL) was suggested more than 30 years ago, but its authenticity has never been formally addressed. We exam IntroductionChronic lymphocytic leukemia (CLL) is the most common leukemia of adults in Western countries and accounts for ϳ 30% of all cases of leukemia in the United States. It is a heterogeneous leukemia that is thought to originate from antigen-stimulated B cells that escape from normal cell death mechanisms. 1,2 Survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 49 publications
3
44
0
Order By: Relevance
“…Malignant B cells from patients with chronic lymphocytic leukemia (B-CLL) express much higher levels of FcmR than normal B cells from healthy donors (30,31). Antigenic stimulation through the BCR is thought to promote the outgrowth of B-CLL (32,33), and our results suggest that elevated FcmR expression may enhance a BCR-triggered survival signal and contribute to the pathogenesis of B-CLL.…”
Section: Discussionmentioning
confidence: 68%
“…Malignant B cells from patients with chronic lymphocytic leukemia (B-CLL) express much higher levels of FcmR than normal B cells from healthy donors (30,31). Antigenic stimulation through the BCR is thought to promote the outgrowth of B-CLL (32,33), and our results suggest that elevated FcmR expression may enhance a BCR-triggered survival signal and contribute to the pathogenesis of B-CLL.…”
Section: Discussionmentioning
confidence: 68%
“…Because the half-life of the injected IgM is the same in Fcmr KO and WT control mice, FcμR does not appear to be involved in IgM catabolism likely mediated by LSECs, but rather is involved in the production and/or secretion of IgM by B and/or plasma cells. In humans, chronic lymphocytic leukemia (CLL) B cells overexpress cell surface FcμR and rapidly ingest IgM ligands through this receptor (20,21). Curiously, as many CLL patients have reduced serum Ig levels including IgM, it would be worthwhile to determine whether this reduction is related to the enhanced expression of FcμR on the leukemic B cells.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be elucidated how FcμR-mediated signals cooperate with BCRderived signals to promote B-cell survival. Interestingly, it was recently reported that the malignant B cells from patients with chronic lymphocytic leukemia (CLL) express much higher levels of FcμR than normal B cells from healthy donors (33). It is widely believed that the initial expansion and prolonged survival of the CLL B-cell clone are driven by self-antigen (34).…”
Section: (Unpaired T Test) (D)mentioning
confidence: 99%